The countryside of Hospitaller Rhodes 1306-1423 original texts and English summaries - Luttrell, Anthony 1932-; O'Malley, Gregory (Routledge, Taylor & Francis Group, 2019)
"The Countryside of Hospitaller Rhodes 1306-1423 explores the main themes of settlement, population and defence of the island of Rhodes from 1306 through to 1423, approximately halfway through the period of Hospitaller rule. Based largely on the Hospital's Rhodian archive, this book is the scientific presentation of 208 documents brought together with detailed English summaries to further help readers understand the documents and their technical features. The Countryside of Hospitaller Rhodes is ideal for academics and postgraduates of the Crusades"...
Includes bibliographical references and index
Keywords: Johanniterorden; Geschichte 1306-1423; Hospitalers -- Greece -- Rhodes (Island) -- History -- To 1500; Landschaft; Rhodes (Greece : Island) -- History; Rhodos; Quelle